Printing Life‐Inspired Subcellular Scale Compartments with Autonomous Molecularly Crowded Confinement. Issue 7 (3rd May 2019) - Arrabito, Giuseppe; Cavaleri, Felicia; Porchetta, Alessandro; Ricci, Francesco; Vetri, Valeria; Leone, Maurizio; Pignataro, Bruno
Abstract: A simple, rapid, and highly controlled platform to prepare life‐inspired subcellular scale compartments by inkjet printing has been developed. These compartments consist of fL‐scale aqueous droplets (few µm in diameter) incorporating biologically relevant molecular entities with programmed composition and concentration. These droplets are ink‐jetted in nL mineral oil drop arrays allowing for lab‐on‐chip studies by fluorescence microscopy and fluorescence life time imaging. Once formed, fL‐droplets are stable for several hours, thus giving the possibility of readily analyze molecular reactions and their kinetics and to verify molecular behavior and intermolecular interactions. Here, this platform is exploited to unravel the behavior of different molecular probes and biomolecular systems (DNA hairpins, enzymatic cascades, protein‐ligand couples) within the compartments. The fL‐scale size induces the formation of molecularly crowded confined shell structures (hundreds of nanometers in thickness) at the droplet surface, allowing discovery of specific features (e.g., heterogeneity, responsivity to molecular triggers) that are mediated by the intermolecular interactions in these peculiar environments. The presented results indicate the possibility of using this platform for designing nature‐inspired confined reactors allowing for a deepened understanding of molecular confinement effects in living subcellular compartments. Abstract : A mild inkjet‐printing approach allow for aqueous droplets downscaling to the femtoliter scale, triggering the formation of self‐selected submicrometer‐thin molecular or biomolecular structures at the water/oil interface. Molecular probes (jointly with fluorescence lifetime (τ) imaging) allow for a thorough characterization of this artificial environment, revealing unique features (reduced water content, molecular crowding, molecular proximity, spatial localization) that closely mimic subcellular crowded compartments.